Acceptance of a flipped classroom to improve university students’ learning: An empirical study on the TAM model and the unified theory of acceptance and use of technology (UTAUT) - Ibrahim Youssef Alyoussef (Heliyon, 2022)
Higher education has given the flipped classroom a lot of attention as a result of its pedagogical success. As a result of the adoption of social media, smartphones, and computers in the classroom, new strategies for providing online courses, such as flipped classrooms, have evolved. To further understand the effects of such technology integration in teaching, the study looked at the responses of 213 undergraduate students at King Faisal University. For a semester, participants took their regular classes in a flipped classroom. The participants answered a survey made expressly for this study to find out if they would still be willing to use flipped classes following this experience. A structural equation modeling approach was used to analyze the research paradigm, which is based on the technological adoption model. The findings demonstrated that each variable category had a favorable influence on perceived usefulness and perceived ease of use. Perceived utility and ease of use serve as mediating elements in the relationship between independent variables and attitudes toward adopting flipped classrooms. Additionally, the findings indicated that ATFC and BIFC have a positive influence on the acceptance of flipped classrooms. In terms of education and learning, the utilization of classroom instruction is positively impacted by both ATFC and BIFC. These findings show that attitudes toward blended learning and intentions to use flipped classrooms have the biggest impacts on the adoption of the concept in Saudi Arabia higher education.